Effects of behavioural parent training programme with and without teacher intervention on attention-deficit / hyperactivity disorder (ADHD) symptoms among ADHD children in Iran - Shaban, Sepideh (2014)
Previous studies have shown that Attention-Deficit/Hyperactivity Disorder (ADHD) among children is a chronic disorder that may adversely affect individuals throughout their lives. Children with ADHD often have problematic parent-child interactions and academic and behavioral problems at school. Studies conducted in Iran between 2009 and 2013 have found that the prevalence rates of ADHD among children have increased. Currently, efforts to reduce ADHD symptoms have focused on parenttraining and/or medical interventions. This experimental study was conducted to compare the effects of behavioral parent-training (BPT) combined with teacher intervention and BPT-only on ADHD symptoms among children from counseling centers in Tehran, Iran. Using a randomized, pre-test, post-test, control group design, 96 boys and girls aged between 9 to 11 years old were randomly assigned into two intervention and one control groups. The two interventions were: (1) Barkley’s Behavioral Parent Training Program for parents (BBPT), and (2) BBPT combined with School Intervention for teachers. The Children’s Symptom Inventory (CSI4) and Teacher Report Form (TRF) were used to measure outcome variables. Mothers and teachers participated in the intervention programs. Descriptive and inferential statistics were applied to analyze the data and test hypotheses. Additionally, a semi-structured interview with three parents and three teachers from each experimental group was conducted to gain greater understanding of the results. Overall, Two-way Repeated Measures ANOVA was conducted to study the effects of groups across test. The results showed that the average mean score for inattention symptoms as measured using CS14 was significantly different among the three groups, (F (4,93)=16.786, p=.001). Similar result was achieved for inattention score as measured using TRF, (F (4,93)=11.668, p=.001). The average mean score for hyperactivity-impulsivity measured by CSI4 across time (test) was also significantly different among the three groups, (F (4,93)=14.738, p=.001). Similar results were also obtained for the mean score of hyperactivity-impulsivity measured using TRF, (F (4, 93) = 5.037, p = .001). Results also show that interaction between groups and test for inattention with hyperactivity-impulsivity score in CSI4 (F (4, 93) =19.805, p = .001) and TRF (F (4, 93) = 19.805, p = .001) were significant. Hence, this study found that both interventions, namely, Barkley’s Behavioral Parent Training combined with Teacher Intervention and BPT-only were both effective in reducing symptoms of ADHD among Iranian children at home and school settings. The descriptive results of the semistructured interview presented parents’ and teachers` satisfaction from children`s behavior after implementing the interventions. This study tested the effects of parent and teacher training to improve ADHD symptoms among children in Iran. One suggestion for future studies is to provide direct intervention to ADHD children, in addition to parent and teacher involvement in order to achieve more comprehensive outcomes. Inclusion of a qualitative component in future experimental studies may provide deeper understanding of the strengths and weaknesses of interventions.